KNOWLEDGE OF DIABETIC RETINOPATHY AMONGST TYPE II DIABETES MELLITUS PATIENTS IN DR. WAHIDIN SUDIROHUSODO HOSPITAL - Nursyamsi Nursyamsi; Habibah Setyawati Muhiddin; Gonardy Jennifer (Nusantara Medical Science Journal, 2018)
Introduction: Diabetic retinopathy (DR) is the leading cause of blindness that rises significantly each year  along with the increasing diabetic population. It is estimated that 1 out of 3 people with diabetes will suffer from DR and 1 in 10 of them will be threatened with blindness. The main problem on DR management is the delay in diagnosis since most patients in the early stages do not experience visual impairment.Methods: Descriptive research was conducted over three months on 175 patients diagnosed with type 2 Diabetes Mellitus (DM) within the Internal Medicine Clinic at Hasanuddin University Hospital. Self-administered questionnaires were used to assess knowledge of DR amongst the diabetic patients.Results: The level of DR knowledge among type 2 DM was split into three categories. The level of knowledge on DM complication was within the good category for 109 patients (61.6%), whilst the level of knowledge on DR screening was within the the sufficient category for 150 patients (84.7%) and knowledge on DR management was within the good category for 98 patients (55.4%). Although the level of knowledge was categorized good for the majority of respondents, the remaining 45 (25.4%) respondents had never done DR screening, and most patients (57.1%) believed that DM patients tend not to screen due to the lack of knowledge about DR.Conclusion: In general, patients with type 2 DM have a good level of knowledge about diabetic retinopathy.